Study Of The Synthesis Of The Sex Pheromone Of The European Corn Borer (Ostrinia Nubilalis) - Turgunboy Dzhumakulov; Zhakhongir Eralievich Turdibaev; Laziz Tashpulatovich Yuldashev (Genius Publishing Group, 2025)
The European corn borer (Ostrinia nubilalis) is one of the key phytophagous pests in the agroecosystems of Europe and North America. One of the promising methods of its control is the use of sex pheromones for monitoring and communication disruption strategies. This paper examines the biochemical and molecular mechanisms of sex pheromone synthesis in O. nubilalis, as well as the analytical methods used. The data obtained contribute to improving the effectiveness of pheromone traps and developing genetically grounded approaches for population control. The use of sex pheromones in integrated pest management systems necessitates the development of practical synthesis schemes, enabling the production of corn borer pheromones (Ostrinia nubilalis Hbn.) from common precursor compounds—synthons.
Keywords: pheromones; pest; caterpillar